Mystery Box? Magic Box? or "Lambe-Lambe Theater"?: Naming the Gazes in the Genealogy of Xalapa (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The artists of Xalapa have recognized a genealogy by designating their own work. That recognition implies a model of the character and purpose of their poetics. To distinguish or assimilate their work with other expressions of puppetry arts, they assume models pursuing technical resolutions and poetic configurations. This paper reflects on the difference and the similarities around the comprehensions of looking since they affect the understanding of a scenic device that, commonly, can be named in three different ways: Mystery Box, Magic Box and Lambe Lambe Theater.